COVID-19 Incidence in Europe: Drivers and Government Interventions - Dan Lupu; Liviu George Maha; Elena Daniela Viorică (Transylvanian Review of Administrative Sciences, 2020)
This study aims to identify the determinant country-level factors that impact the trend of registered death cases from the recently emerged infectious disease COVID-19, analyzing data from March 2020 to July 2020, for 40 European countries. We use four categories of indicators covering major areas of influence: health, demographic, economic, and societal/cultural indicators. We reduce the dimensionality of the data to three latent factors by applying a Principal Component Analysis method, and we employ a multiple linear regression model to estimate the effects of these factors on the trend of death rates. The main result of the study is that a decreasing trend of death cases is the effect of a functional and citizen-oriented state, and is not only impacted by characteristics of the medical system or by individual features. Our findings also suggest that the premises for a low mortality rate are built by policies that have effects in the long- and medium- term. These policies refer to economic growth, sustainable development, healthcare, and the creation of a stable political system and an efficient administration.